The reconstructed evolutionary history of the Engelhardia spicata complex highlights the impact of a three‐tiered landform in the Indo‐Burma ecoregion - Zhang, Can‐Yu; Cao, Guan‐Long; Hu, Jian‐Lin; Huang, Pei‐Han; Li, Min; Su, Ren‐Ping; Fang, Ou‐Yan; Cai, Xiang; Song, Yi‐Gang; Hu, Guo‐Xiong; Xie, Kai‐Qing; Li, Lang; et al. (American journal of botany, 2025)
Premise The lateral displacement of the Indochina Peninsula, driven by the Indian–Asian plate collision, significantly altered the topography of the Indo‐Burma ecoregion, affecting its climate and biological evolution. Despite the renowned biodiversity of the region, spatiotemporal patterns of evolution remain poorly understood. Methods We analyzed the Engelhardia spicata complex, which has a continuous distribution across Indo‐Burma, based on a robust phylogenetic framework comprising 778 individuals from 80 populations, to elucidate spatiotemporal and paleogeological patterns of evolution. We used ancestral area reconstruction to reconstruct the historical biogeography of the species complex and to understand the broader evolutionary history of the Indo‐Burma ecoregion. Results An initial divergence within the E. spicata complex approximately 26.62 million years ago (Ma) separated a lineage in the Truong Son Mountain Range from one in the Hengduan Mountains and the Shan Plateau. The Shan Plateau and Hengduan Mountain lineages subsequently diverged around 23.03 Ma. These results highlight a three‐tiered landform in the Indo‐Burma ecoregion, characterized by high‐elevation northern regions (Hengduan Mountains, Yunnan‐Guizhou Plateau), intermediate‐elevation central plateau (Shan Plateau), and low‐elevation southern ranges (southern Truong Son Mountains). Conclusions Our findings support the tectonic hypothesis that crustal thickening and lateral extrusion of Indochina occurred simultaneously during the Late Oligocene, which led to the formation of the Indo‐Burma ecoregion and highlights the biological significance of the resulting three‐tiered landform (north‐to‐south altitudinal gradients) in these regions, providing novel insights into biogeographic patterns in Southeast Asia.